HUBUNGAN KEBIASAAN MINUM KOPI DENGAN KADAR HEMOGLOBIN PADA PENGUNJUNG KEDAI “SEDERHANA KOPI” SURAKARTA - Gilang Firmansyah Hidayat; Endang Widhiyastuti (Journal of Indonesian Medical Laboratory and Science, 2022)
Consumption of coffee in Indonesia has increased every year. This is what makes the trend of coffee drinkers continue to increase. There are caffeine in coffee which are an iron absorption inhibitor where caffeine binds iron so it cannot be absorbed by the body. Iron was required in the synthesis of hemoglobin. Reduced hemoglobin levels can cause anemia. The limit of male hemoglobin levels for diagnosing anemia is when the hemoglobin level was less than 13 g/dl. This study aims to determine the relationship between habits drinking of coffee with hemoglobin levels in visitors to the "Sederhana Kopi" Surakarta Shop. The type of this research was observational analytic with cross sectional approach. The time of the study was carried out in February - June 2021. The sample in this study was 30 samples with a total sampling technique. After conducting research on 30 respondens, the results of the study using the Repeated One Way Anova test obtained a significance value of 0,302 (p <0,05) and a correlation value of  0,302.  From the results, it can be concluded that there is no significant relationship between habits drinking of coffee and hemoglobin levels in visitors to the "Sederhana Kopi" Surakarta shop.